International viewpoints - WRENmedia (Technical Centre for Agricultural and Rural Cooperation, 2008)
Four scientists working in Nigeria, Ghana, Rwanda and Sri Lanka comment on why they believe many indigenous African crops became neglected and forgotten. This may have been because they were difficult to process, or because of the promotion of exotic species. With new technologies, processing problems can now be overcome. As a result, these neglected crops deserve to be looked at again, particularly as they are often more resilient than exotic crops in the face of drought or flooding.